1999
DOI: 10.1063/1.123106
|View full text |Cite
|
Sign up to set email alerts
|

Control of silica cap properties by oxygen plasma treatment for single-cap selective impurity free vacancy disordering

Abstract: By exposing the SiO2 films used as annealing caps in the process of impurity free vacancy disordering (IFVD) to an oxygen plasma, which is produced in a reactive ion etching machine, the effect of the exposed caps on quantum well intermixing can be substantially controlled. The effect of the oxygen treatment is manifested in inhibiting the Ga outdiffusion from GaAs/AlGaAs heterostructures. A selective IFVD process using identical silica caps has been obtained by selective exposure of the caps to oxygen plasma.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 17 publications
0
13
0
Order By: Relevance
“…2 Previous works reported that porosity in the dielectric cap determine the wavelength shifts of the QW structure. 3,4 The sol-gel process is a commercially promising technology compared with other thin film technologies, with advantages such as low cost, ease of doping variation, and high homogeneity of multicomponent oxide films. It is well known that sol-gel derived films are porous under moderate heat-treatment temperatures.…”
mentioning
confidence: 99%
“…2 Previous works reported that porosity in the dielectric cap determine the wavelength shifts of the QW structure. 3,4 The sol-gel process is a commercially promising technology compared with other thin film technologies, with advantages such as low cost, ease of doping variation, and high homogeneity of multicomponent oxide films. It is well known that sol-gel derived films are porous under moderate heat-treatment temperatures.…”
mentioning
confidence: 99%
“…The properties of SiO 2 may have a great effect on enhancing QW intermixing. 16 The spin-on silica film can reduce the threshold temperature at which significant QW intermixing takes place. From previous studies, it is clear that, compared to a bare surface, the oxidation of GaAs surface can enhance the QW intermixing.…”
Section: Qw Intermixng Resultsmentioning
confidence: 99%
“…Selective-area QWI is a very promising technique for the realization of monolithically integrated devices. To date, a number of QWI techniques have been reported, including impurityinduced disordering (Ooi et al 1994), impurity-free vacancy-induced disordering (IFVD) (Helmy et al 1999), ion implantation-induced inter-diffusion (Wan et al 1997), and several laser-induced disordering processes (Ralston et al 1987). IFVD is usually implemented by the deposition of a dielectric film coating followed by rapid thermal annealing (RTA).…”
Section: Introductionmentioning
confidence: 98%